PENGARUH IMPLEMENTASI MODEL PEMBELAJARAN KONTEKSTUAL BERBASIS LINGKUNGAN TERHADAP MINAT DAN HASIL BELAJAR IPA SISWA SD (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Abstract This study aims to determine the effect of environmental-based contextual learning models on students' interest and learning outcomes in science. This research is a quasi-experimental research with The Posttest-Only Control-Group Design. The research population was all fifth grade students of SD Negeri 2 Tribuana. The sample was determined by group random sampling technique. The sample in this study amounted to 42 people. Data on student interest in learning was collected by using a questionnaire and learning outcomes using multiple choice tests. Data were analyzed using MANOVA (Multivariat Analysis of Variance) assisted by SPSS 17.00 for windows. The results of the study indicate that: First, there is a significant difference in learning interest between students who study with environment-based contextual learning and students who study with conventional learning models in fifth grade students of SD Negeri 2 Tribuana. Second, there are significant differences in science learning outcomes between students who study with environment-based contextual learning and students who study with conventional learning models in fifth grade students of SD Negeri 2 Tribuana. Third, Simultaneously there is a significant difference in interest in learning and science learning outcomes between students who study with environment-based contextual learning and students who study with conventional learning models in fifth grade students of SD Negeri 2 Tribuana. Keywords: environment-based contextual learning, interest in learning, and science learning outcomes.